The scientific enlightenment of mathematics teachers and its relationship to the achievement of their students for mathematical concepts (Journal of the College of Basic Education, 2023)
Summary of the research:The objective of the current research is to identify the scientific enlightenment of mathematics teachers and its relationship to their students' achievement of mathematical concepts, and to achieve the goal of the research, the descriptive correlational approach was adopted. Male and female students in the primary schools affiliated to the General Directorate of Education of Baghdad, Rusafa, for the academic year (2021-2022), the researcher prepared two tests, one of which is for scientific enlightenment in mathematics according to the following dimensions (mathematical knowledge, the nature of mathematics and the history of its development), consisting of (40) items of the type Multiple choice, and its validity and reliability were verified. The second was an achievement test of mathematical concepts for fifth grade students, which consisted of (30) items of multiple choice type. Its validity and reliability were verified, and after processing the data statistically using the Pearson correlation coefficient and the t-test to reveal the significance of the differences. For the correlation coefficients between scientific enlightenment and achievement, the results of the statistical analysis showed that most of the mathematics teachers possess scientific enlightenment at an acceptable level, as well as the existence of a strong direct correlation between the scientific enlightenment of mathematics teachers and the achievement of their students for mathematical concepts. conclusions and put forward a number of recommendations and proposals.Keywords: scientific enlightenment, mathematics, mathematical concepts.